Dasar-Dasar Bahasa Arab bagi Siswa MI - Irawan, Vaesol Wahyu Eka (MOMENTUM : Jurnal Sosial dan Keagamaan, 2024)
MI students are students who like to play rather than receive lessons. They are among the students who switched from kindergarten to MI. No wonder they play a lot even in the classroom compared to listening and focusing on the lesson. Among the lessons that are quite captivating for MI students is Arabic. Arabic Language Lessons are Islamic Religious Education Lessons. MI students need an early introduction to Arabic language materials. This study uses qualitative research with the type of literature research. The data analysis method uses descriptive analysis, while the data collection method uses documentation. This research obtained the result that MI students need an introduction to Arabic. Introducing Arabic to MI students starts from the basic vocabulary in Arabic. Like the vocabulary of human limbs, Arabic introduces oneself, and greets others. In an effort to introduce and strengthen the memorization of Arabic vocabulary, students can use strategies and methods that are relevant to learning. MI students focus on memorization activities, the more students memorize, the easier it is for children to understand and memorize Arabic texts. MI students prefer to memorize using songs, so teachers are responsible for developing student memorization methods through memorization of songs that contain Arabic vocabulary